Influence of catalytic systems in Stille polymerization on the electrochromic performance of diketopyrrolopyrrole-based conjugated polymers. (22nd December 2017) - Neo, Wei Teng; Ye, Qun; Shi, Zugui; Chua, Soo-Jin; Xu, Jianwei
Abstract : Polymers with better structural regularity exhibit larger optical contrasts, higher coloration efficiencies and faster switching times. Abstract : Two diketopyrrolopyrrole- (DPP) and thienothiophene-based donor–acceptor (D–A) type conjugated polymers are separately synthesized using Stille coupling reactions with Pd(PPh3 )4 and PdCl2 (PPh3 )2 catalytic systems, respectively. The influence of the catalyst employed on the structural regularity of the resulting polymers, and their subsequent electrochromic (EC) performances are investigated. Marked differences in the optical contrasts, switching times, coloration efficiencies and redox stabilities of the polymers are uncovered. For example, polymerP1, which is prepared using Pd(PPh3 )4 as a catalyst, exhibited a larger optical contrast and coloration efficiency by 40% and 79%, respectively, and a faster coloration time by 55%, at 825 nm, than its counterpart polymerP2, which is prepared using PdCl2 (PPh3 )2 . The intrinsic optical, electrochemical and morphological properties of the polymers are characterized, revealing that the physical conformation and packing of the polymer chains are the main factors causing the discrepancy in EC performances.